2017
DOI: 10.1631/jzus.b1600573
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the IGF1 gene and their association with growth traits, serum concentration and expression rate of IGF1 and IGF1R in buffalo

Abstract: The insulin-like growth factor 1 (IGF1) gene is a member of the group of somatotropin axis genes that play a significant role in cell proliferation and growth of muscles. Here, we searched for polymorphisms in buffalo IGF1 and found two novel single nucleotide polymorphisms (SNPs), G64A and G280A, in the noncoding sequences of exon 1 and exon 4, respectively. Statistical analysis of different genotypes showed that the individuals with GG genotypes had significantly (P<0.05) higher body weight (BW) and average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 33 publications
3
11
0
Order By: Relevance
“…Clearly, the GH-IGF system is highly responsive to growth selection; specific effects have been described on the level of DNA, mRNA, and protein with respect to the GH-IGF system in model animals or farm animals [11][12][13][14][15], and many of these studies have particularly addressed the biomarker potential of IGF-1 or assessed single time points. In human subjects, longitudinal concentrations have been provided both for IGF-1 [16] and for IGFBP-3 [17].…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, the GH-IGF system is highly responsive to growth selection; specific effects have been described on the level of DNA, mRNA, and protein with respect to the GH-IGF system in model animals or farm animals [11][12][13][14][15], and many of these studies have particularly addressed the biomarker potential of IGF-1 or assessed single time points. In human subjects, longitudinal concentrations have been provided both for IGF-1 [16] and for IGFBP-3 [17].…”
Section: Introductionmentioning
confidence: 99%
“…On contrary, Khederzadeh and Yazdanpanah (2013) observed three different SSCP patterns in amplified 265-bp of IGF-1 promoter region collected from five cities in Khuzestan province of Iran. Moreover, two novel single nucleotide polymorphisms (G64A and G280A) in the non-coding sequences of IGF-1 exon 1 and exon 4 of Egyptian buffaloes were detected by El-Magd et al (2017).…”
Section: Resultsmentioning
confidence: 98%
“…This study is part of a broader project targeting the genetic improvement of the of Egyptian water buffaloes. We previously screened IGF1, IGF1R, IGF2, IGF2R, and Cyp19A1 for polymorphisms and analyzed their associations with growth traits and fertility [15,16,18,24,26]. Herein, we extended our investigation to identify genetic variations in the GHR gene and determine their potential effects on milk production traits.…”
Section: Resultsmentioning
confidence: 99%
“…Again, Shi et al [13] did not study the effect of this important SNP on milk production and milk quality traits in buffaloes. Although many studies reported the ability of noncoding polymorphisms including: synonymous, intergenic and intronic SNPs to modify complex traits in animals [14][15][16], it is still essential to study non-synonymous SNPs, as they could directly alter the amino acids sequence, which could possibly lead to phenotypic variation. Therefore, in this study, we screened coding sequences of E4-E6 and E8 for polymorphisms.…”
Section: Introductionmentioning
confidence: 99%